2022
DOI: 10.3390/pathophysiology29030027
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preoperative Atorvastatin or Rosuvastatin Use in Adult Patients before CABG Does Not Increase Incidence of Postoperative Acute Kidney Injury: A Propensity Score-Matched Analysis

Abstract: Background: Acute kidney injury (AKI) is among the expected complications of cardiac surgery. Statins with pleiotropic anti-inflammatory and antioxidant effects may be effective in the prevention of AKI. However, the results of studies on the efficacy and safety of statins are varied and require further study. Methods: We conducted a retrospective cohort study to evaluate long-term preoperative intake of atorvastatin and rosuvastatin on the incidence of AKI, based on the “Kidney Disease: Improving Global Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…As a result, statins have been proposed as a potential modulator of clinical outcomes after surgery 8 . In particular, some observational studies suggested that statins may be associated with a reduced risk of acute kidney injury (AKI) after cardiac surgery 9 , although this has not been a consistent finding 10,11 . Any effect on postoperative AKI is relevant as this complication affects as many as 25-30% of patients after cardiac surgery 12,13 and is associated with longer hospital stay and increased risk of mortality [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, statins have been proposed as a potential modulator of clinical outcomes after surgery 8 . In particular, some observational studies suggested that statins may be associated with a reduced risk of acute kidney injury (AKI) after cardiac surgery 9 , although this has not been a consistent finding 10,11 . Any effect on postoperative AKI is relevant as this complication affects as many as 25-30% of patients after cardiac surgery 12,13 and is associated with longer hospital stay and increased risk of mortality [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%